Non-stationary twisting of an elastic bar with viscoplastic external resistance - Shatsky, I. P.; Perepichka, V. V. (Reports of the National Academy of Sciences of Ukraine, 2014)
The problem of non-stationary twisting of a semiendless elastic rod interacting with the medium is considered, using the model of viscoplastic friction. An exact analytical solution of the problem is obtained for an arbitrary moment of time from the beginning of a perturbation. The analysis of the obtained results for the moved part of the rod is performed.